اتجاهات الطلبة نحو تخصص الأرطوفونيا وعلاقتها بدافع الإنجاز الدراسي لدى طلبة السنة الثالثة أرطوفونيا - شلابي,سهيلة (University of Eloued جامعة الوادي, 2024)
- ملخص: تهدف الدراسة إلى الكشف عن العلاقة بين اتجاهات الطلبة نحو تخصص الأرطوفونيا ودافع الإنجاز الدراسي، بالإضافة إلى التعرف على طبيعة اتجاهات الطلبة نحو تخصص الأرطوفونيا والتعرف على مستوى دافع الإنجاز الدراسي لدى عينة الدراسة، وتكونت عينة الدراسة من 101 طالبا تم اختيارهم بطريقة قصدية، وطبق عليهم مقياس خاص باتجاهات الطلبة نحو التخصص الأرطفونيا ومقياس دافع الإنجاز الدراسي، أسفرت النتائج على أنه توجد علاقة إرتباطية بين اتجاهات نحو تخصص الأرطوفونيا ودافع الإنجاز الدراسي بالإضافة إلى وجود اتجاهات ايجابية ودافعية انجاز مرتفعة لدى عينة الدراسة. Abstract : This study examines the relationship between student attitudes towards their Speech Therapy major and academic achievement motivation, in addition to identifying the nature of student attitudes toward the Speech Therapy major and identifying the level of academic achievement motivation among the study sample. A purposive sample of 101 third-year students was utilized for the research. Data was collected using a specialized scale designed to measure student perceptions of the Speech Therapy major and motivation of Academic achievement scale. The results showed that there is a correlation between attitudes of students towards their major and academic achievement motivation,in addition to the presence of positive attitudes and high achievement motivation among students pursuing Speech Therapy.
Keywords: Student Attitudes; Speech Therapy Major; Academic achievement motivation; الاتجاهات; الأرطوفونيا